Challenges of managing maritime cultural heritage in Asia in the face of climate change - Daly, Patrick (2023)
Changing weather patterns, increasing frequency and intensity of natural hazards, and rising sea levels associated with global climate change have the potential to threaten cultural heritage sites worldwide. This is especially the case for maritime heritage sites located in the low-lying coastal and delta regions of Asia. Maritime heritage can reflect both highly localized cultural products based on the coupling of people and maritime environments and the historic footprints of complex maritime networks that connect people, ideas, and material over vast distances, creating unique cultural spheres. Furthermore, maritime heritage sites potentially serve as or contain records of how past societies have been impacted by and adapted to past environmental stress. Therefore, their degradation threatens local/regional/global cultural patrimony as well as evidence of human resilience and fragility in the face of environmental change. This makes a strong case for urgent preservation. However, the possible damage caused by climate change and the scale of vulnerable maritime heritage pose seemingly insurmountable challenges. In this paper, we present the ways in which maritime heritage sites across Asia are vulnerable to environmental stresses, such as changing sea levels, coastal erosion, flooding, and storm surges. Our objective is to draw upon our experience documenting endangered cultural heritage across South and Southeast Asia to illustrate that there are unique conceptual and practical characteristics of maritime heritage that complicate effective management and conservation efforts on the scale required to prevent massive loss by climate change. We conclude by stressing the need to reconceptualize debates about the custody and stewardship of maritime heritage and the urgency of employing a wide range of innovative preservation solutions to ensure maritime patrimony is not lost to the rising tides.